2009
DOI: 10.2174/1876893800901010030
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of 3.1kb Promoter Region of the Oct4 Gene from the Fischer 344 Rat

Abstract: Here, the role of methylation in regulation of rat Oct4 gene was evaluated during embryonic development, in adult tissues and in embryo-derived cells. First, the region 3.1 kb upstream to the rat Oct4 ATG site was cloned and sequenced. The rat Oct4 upstream sequence was similar to that in bovine, mouse and human with two upstream elements: proximal (PE) and distal enhancers (DE) and four homology conserved regions (CR1-4). The conserved regions in the rat have 69% - 96% homology with bovine, human, mouse seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The genomic regions of Oct4 targeted for bisulfite sequencing, CR1 and CR4, were chosen based on cross-species conservation and correlation between methylation and expression as previously defined (He et al, 2009; Imamura et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…The genomic regions of Oct4 targeted for bisulfite sequencing, CR1 and CR4, were chosen based on cross-species conservation and correlation between methylation and expression as previously defined (He et al, 2009; Imamura et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…Potential-To determine whether PKCi could maintain previously established rESC lines in an undifferentiated state, we cultured an F344 rESCs line that expresses EGFP under the control of a 3.1-kb portion of the rat Oct4 promoter/enhancer region (4,17). We found that PKCi culture efficiently maintains undifferentiated colony morphology and OCT4-EGFP reporter expression of established rESC lines (Fig.…”
Section: Inhibition Of Pkc Signaling Maintains Rescs In An Undifferenmentioning
confidence: 97%
“…Pbgd was used for quantitative (q)RT-PCR normalization via the DC t method [22]. Reactions for qRT-PCR were run in duplicates and averaged and were also run using 2 or 20 ng per tube cDNA loading concentrations.…”
Section: Semi-quantitative Reverse Transcriptase-polymerase Chain Reamentioning
confidence: 99%
“…Plasmid N1-Oct4-GFP contains a 3.1 kb portion of the rat Oct4 promoter including both the proximal enhancer and a portion of the distal enhancer. The Oct4 promoter and the rat Oct4 ATG site was inserted 5' to GFP, polyA sequence [22]. pN1-Oct4-GFP also contains a neomycin/kanamycin selection cassette under a separate SV40 promoter.…”
Section: Esc Transfectionmentioning
confidence: 99%
See 1 more Smart Citation